Steady-state optimisation of a groove texture with different oil film thickness. (2015) - Zhao, Yuncai; Yang, Fei
The lubricant film thickness is not stable in practical applications of lubricate. This work focuses on hydrodynamic lubrication performance of surface groove texture for a non-stable oil film thickness and use a two-dimensional computational fluid dynamics (CFD) model base on the Navier-Stokes equation to discuss the relation among groove depth D, groove width W and lubricant film thickness H with a specified sliding speed. It is found that there exist optimum design parameters of surface groove texture for a non-stable oil film thickness. The parameters are characterised by groove width W and groove depth D and its values are respectively 0.5 and 0.7. In addition, the optimum value of groove depth D is strongly affected by groove width. When W varies between 0.1 and 0.8, for example, the optimum's depth D ranges from 0.5 to 1. But it has little effect of lubricant film thickness on the optimum value of groove depth.